Creating connections - Shaffer, Amy S. (Kansas State University, 2009)
The proposed site development is situated in the ahupua’a of Honouliuli, in the district of Ewa on the island of Oahu, Hawaii and has been given the name Kaiaulu. Currently the University of Hawaii is planning to expand their campus in the Ewa district. The project site is 500 acres with the university occupying 204 acres. The remaining 296 acres of the site will be a mixed-use residential community. The design of the site addresses two main dilemmas: 1) creating a town-gown relationship between the university and surrounding mixed-use community and 2) promote the use of the two transit stations that will be located on the site for the new light rail system that will be implemented on the island in the next few years. To better understand the relationships between the institution and the surrounding neighborhood communities and how to successfully incorporate light rail stations into the communities, research was conducted to address the issues stated above. Literature was reviewed with a focus on the guidelines, principles, terms, and relative issues on each topic. Two precedent studies were then conducted relating to town-gown relationships and the implementation of light rail systems and stations. The program and the placement of the transit stations, the institution, and the mixed-use communities were based on the site inventory and analysis of the existing site. With the strategic placement of the transit stations and the university campus, students and residents of the surrounding community are encouraged to interact. Additionally, by making the transit stations welcoming, convenient, and safe, the light rail encourages the students and residents of the communities to lessen the use of their automobiles and use the public transit as a means of reaching their destinations around the island. The design of Kaiaulu brings the students of the institution and the residents and visitors of the surrounding communities together and creates a strong town-gown relationship.
Keywords: Hawaii; Transit; Mixed-use; Campus; Light rail; Landscape Architecture (0390)